Comparison of spring barley (Hordeum vulgare L) varieties grown in organic trials: lodging and plant height - Tomasz Lenartowicz; Henryk Bujak; Marcin Przystalski; Kamila Nowosad; Krzysztof Jończyk; Beata Feledyn-Szewczyk (Agricultural and Food Science)
Lodging is one of the main factors influencing yield reduction in both organic and conventional systems. In the organic system, lodging is mainly controlled by selecting varieties with increased resistance to lodging, by regulating sowing density, or by cultivation of varieties of appropriate height. The present study aimed to compare ten varieties tested in the years 2020–2022 in organic trials in terms of plant height and resistance to lodging in two growth phases (milk and harvest). Depending on the analyzed trait, a linear or cumulative link linear mixed model was fitted on plot data. The analyses showed that variety Farmer was the most resistant to lodging in the two growth phases, whereas varieties KWS Vermont and Rubaszek were less resistant to lodging in two growth phases than Farmer, but only at the milk phase, the differences were significant. Furthermore, Radek was the tallest among the tested varieties, whereas Farmer was classified as mid-tall. According to Wricke’s ecovalence coefficient, Bente was the most stable, while Farmer ranked third. Therefore, varieties that are the most resistant to lodging and are the most stable in terms of height, should be promoted for cultivation.